The impact of adoption of milk safety practices on food and nutrition security: Evidence from smallholder dairy farmers in Ethiopia - Bekele Wegi Feyisa; Jema Haji; Alisher Mirzabaev (Research in Globalization, 2023)
Despite the progress observed over the past decades, food and nutritional insecurity remain the prominent challenges in Ethiopia. In this respect, improved farming practices and productivity-enhancing agricultural technologies have been identified as pathways out of these problems; these technologies are the priority agenda of the government policy in Ethiopia. Nonetheless, the impact of the adoption of milk safety practices on dairy farmers' food and nutrition security has not yet been addressed, especially at the smallholder farmers' level. The aim of this study was to evaluate the impact of the adoption of milk safety practices on dairy farmers' food and nutrition security in Ethiopia, using primary data collected from 410 dairy farmers. Generalized propensity score matching was used to evaluate the heterogeneous impact of the adoption of milk safety practices on the household food and nutrition security indicators (per capita food consumption expenditure and food consumption score). The findings reveal that the adoption of milk safety practices had a moderate impact on food consumption expenditure but had no significant impact on food consumption score. An ordered probit endogenous switching regression was also used to account for unobserved bias and check the robustness of the generalized propensity score estimates. Accordingly, the results are similar to the generalized propensity score estimates, and unobserved bias was not a problem. In general, the impact of adoption of milk safety practices on food and nutrition security of smallholder dairy farmers is moderate in Ethiopia. This might be because of the high compliance costs with the adoption of milk safety practices and the lack of quality-based pricing systems. Hence, creating an enabling environment, which in turn, encourages the adoption of milk safety practices would help improve positive effects of the adoption of milk safety practices on food and nutritional security.
Keywords: 330; Dairy farmers; Ethiopia; Food and nutrition security; Generalized propensity score; Milk safety practices; Ordered probit endogenous switching regression